The Impact of Religious Tourism on Buddhist Monasteries: An Examination of Nine Temples in Ang Thong - Asawachai, Panot (วารสารอิเล็กทรอนิกส์การเรียนรู้ทางไกลเชิงนวัตกรรม, 2019)
In this research, the impact of religious tourism development on the cultural heritage of sacred Buddhist places is analyzed through an examination of nine temples in Ang Thong and their communities. The research considers strategies that might permit religious tourism development while conserving the cultural heritage significance of the places. The research methodologies of this research is conducted by using literature research, field observation, in-depth interview and participatory research. A review of tourism impacts by assessing and studying nine sacred temples’ cultural heritage is undertaken to develop a practicable approach to promoting and managing tourism sustainably. The research is found that tourism brings positive and negative impacts on Buddhist monasteries and their communities. The major positive impacts are contributions to local development in transportation infrastructure, generation of income and employment, and promotion of local culture. The major negative impacts are inequality of income distribution, seasonal jobs and commercialization or commodification of Buddhism. Cultural heritage education and conservation awareness is needed by abbots, monks and communities. It should be strictly applied as a policy. Moreover, the qualification of selection of monk for the Samanasak must be revised and ability in constructing and promoting material things in the temple compound should not be considered. Furthermore, abbot, monks, host communities, the government sector, tourists, media and the voluntary sector must be involved in safeguarding the culture heritage significance of the nine sacred temples and their communities in order to manage the tourism more sustainably.